COPROLOGICAL STUDY OF TREMATODE INFECTION IN REHABILITATED GREEN TURTLES AT THE TURTLE CONSERVATION AND EDUCATION CENTER BALI - Permadi, Aditia; Adnyana, Ida Bagus Windia; Suartini, I Gusti Agung Ayu (Buletin Veteriner Udayana, 2023)
Trematode infection can affect population dynamics of C. mydas in the wild. Diversification and spatio-temporal dynamics of coastal and marine environments in Indonesia can lead to different trematode community compositions among various populations of C. mydas . This study aims to determine the types of trematodes in C. mydas that live in one feeding ground of the Indonesian waters. The research was conducted at the Turtle Conservation and Education Center (TCEC) Serangan, Bali. Nine juveniles C. mydas with the curved carapace lengths between 41 – 66 cm were observed. The turtles are confiscated by the police from a smuggling attempt to Bali, which was previously caught in the waters around Sapeken Island, East Java. Parasite examination was carried out using the Mini-Flotac® coprology technique in combination with Fill-Flotac®. Eggs were identified based on their morphological and morphometric characteristics and the number of eggs per gram (EPG) of feces was calculated according to available technical guidelines. Trematode eggs found were identical to Learedius learedi (Spirirorchiidae), Diaschistorchis pandus (Pronocephalidae), Octangium sagita (Pronocephalidae), and Enodiotrema megachondrus (Plagiorchiidae). The prevalence of L. learedi and D. pandus was 100%, while O. sagita and E. megachondrus were 77.7% and 66.6%. The highest EPG was found in L. learedi (104±57), followed by D. pandus (42±14), O. sagita (32±28), and E. megachondrus (23±19). Statistically, the mean EPG of L. learedi was significantly higher (P<0.05) from the other three types of parasites, while the EPG density of the three types of parasites other than L. learedi was not significantly different (P>0.05). The result provides an up-to-date baseline information on the type and prevalence of trematodes in C. mydas inhabited Sapeken waters of East Java. Similar studies involving turtle populations from other areas are needed to enhance the understanding of the host-parasite dynamics between turtle population stocks from various waters in Indonesia.